Analisis Tindak Tutur Lokusi dalam Video Pembelajaran Bahasa Indonesia pada Kanal YouTube Arisa Nur Aini - Dita Idmania; Andini Bella Pertiwi; Rizki Ayudika Yulistiani; Rizkamalia Ciptarini Mega Gustami; Salsabila Zain Syafa; Asep Purwo Yudhi Utomo; Dyah Prabaningrum; Ferani Mulianingsih (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Language serves as a fundamental tool for human communication. On social media platforms like YouTube, various forms of expression utilize both direct and indirect language. Language acts as a symbol shaped by human experiences that are intrinsically linked to behavior and action. This concept illustrates that everything in the human mind can be expressed through written and spoken words. This research adopts a descriptive qualitative approach, employing the "simak catat" technique for data collection. The objective is to document locutionary speech acts present in Indonesian language learning videos from Arisa Nur Aini's YouTube channel. A total of 189 locutionary speech acts were recorded, consisting of 130 declarative locutions, 32 interrogative locutions, and 27 imperative locutions. The analysis focuses on both the linguistic and pedagogical aspects that contribute to the teaching and learning process. It emphasizes the impact of speech acts on students' understanding and engagement during learning activities. The findings of this study aim to offer new insights for researchers interested in exploring the dynamics of communication in online learning environments. Additionally, the information gathered can serve as a significant reference for developing more effective teaching methodologies.